Urologist Workforce Variation Across the VHA - Skolarus, Ted A. (Fed Pract, 2015)
Distribution of urologists varies significantly at the facility rather than at the regional level, according to a large-scale study, but regional approaches, e-consults, and telemedicine may mitigate veteran access issues.